Cardiac electrical abnormalities in a mouse model of left ventricular non-compaction cardiomyopathy - Vítor S. Fernandes; Ricardo Caballero; Marcos Siguero-Álvarez; Tania Papoutsi; Juan Ramón Gimeno-Blanes; Eva Delpón; José Luís de la Pompa (PLoS ONE, 2025)
Mutations in MINDBOMB 1 ( MIB1 ), encoding an E3 ubiquitin ligase of the NOTCH signaling pathway, cause left ventricular noncompaction cardiomyopathy (LVNC) in mice and humans, increasing the risk of arrhythmia and left ventricular dysfunction. This study aimed to investigate the effect of MIB1 mutations on cardiac electrical activity. We examined male Mib1 flox ;Tnnt2 Cre mice, a disease model of LVNC, and wildtype littermates on the C57BL/6J genetic background. Our results demonstrate that the gap-junction protein connexin43 was delocalized from the intercalated disks to the lateral long axis of Mib1 flox ;Tnnt2 Cre cardiomyocytes. Cardiomyocyte electrophysiology revealed an increase in the Na (I Na ) peak density at potentials between -50 and -30 mV in Mib1 flox ;Tnnt2 Cre mice, with no changes in I Na activation or inactivation kinetics. Mib1 flox ;Tnnt2 Cre cardiomyocytes also showed decreases in outward K + peak currents and currents at the end of depolarizing pulses at potentials ≥−10 mV and ≥−20 mV, respectively, and this was accompanied by a lower charge density at ≥−20 mV. Action potential duration was increased in Mib1 flox ;Tnnt2 Cre cardiomyocytes. The cardiac stress, induced by swimming endurance training or β-adrenergic stimulation with isoproterenol, increases QTc duration in Mib1 flox ;Tnnt2 Cre mice, accompanied by a decrease in T-wave amplitude and area. Swimming endurance training decreased heart rate in wildtype and Mib1 flox ;Tnnt2 Cre mice but was unaffected by long-term isoproterenol treatment. These mouse findings are in agreement with an increased QTc duration found in LVNC patients carrying MIB1 mutations. These results provide insight into the outcomes of LVNC and relate its pathogenicity to impaired ventricular repolarization.